Mencegah Trauma Pasca Bencana Gempa Bumi pada Anak dengan Terapi Rekreasional di Lombok Utara - Rias Pratiwi Safitri; Joko Jumadi; Fitri Romadonika; Eka Adithia Pratiwi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Earthquakes that have occurred consecutively in Lombok since July 29, 2018, have had a tremendous impact on all aspects of the lives of disaster victims, both physical, social, and psychological aspects. Various children's reactions to disasters according to the American Academy of Child and Adolescent Psychiatry (AACAP) depend on the damage suffered during the disaster. The death of a family member or friend is very traumatic, followed by the loss of family homes, schools, pets, and damage to the community. Therefore, efforts to implement recreational therapy in the form of fun-based games and games education is needed to help mental recovery of children, so as to prevent continuing trauma. After doing recreational therapy in 20 villages, it shows positive changes for the children to be more cheerful and require continuous therapy, especially those that support children's education and visual-motor skills.